Analisis Kendala Guru dalam Penerapan Kurikulum Merdeka di Sekolah Dasar - Dita Afianti; Rahayu Condro Murti (PT. Anagata Sembagi Education, 2024)
This study aims to find out how the inhibiting factors become obstacles for teachers in implementing the independent learning program at SDN 2 Sanden. This research is descriptive qualitative research with the determination of informants using a purposive sampling technique. The sources of information for this research consisted of four class teachers and the school principal. Data collection techniques using interviews and observation. Test the validity of the data using the credibility test of the source triangulation technique. The data obtained was then analyzed using the Miles and Hurbermen technique or model which consists of data reduction, data presentation, drawing conclusions and verification. The results showed that there were many problems implementing the independent curriculum, one of which was the teacher's constraints in implementing the independent curriculum. The obstacles included difficulties in preparing learning tools according to the independent curriculum guidelines, lack of facilities and infrastructure, and teachers have difficulty adapting to the Independent Curriculum. Change cannot be obtained instantly, good cooperation is needed between all parties, both teachers, school principals, agencies, parents, and other related parties. The independent curriculum is expected so that students can develop according to their potential and abilities.